A Massive Suspension Culture System With Metabolic Purification for Human Pluripotent Stem Cell‐Derived Cardiomyocytes. (29th October 2014) - Hemmi, Natsuko; Tohyama, Shugo; Nakajima, Kazuaki; Kanazawa, Hideaki; Suzuki, Tomoyuki; Hattori, Fumiyuki; Seki, Tomohisa; Kishino, Yoshikazu; Hirano, Akinori; Okada, Marina; Tabei, Ryota; Ohno, Rei; et al.
Abstract : Pluripotent markers such as Oct3/4 and Tra‐1‐60 were expressed in embryoid bodies 2 weeks after differentiation in the massive suspension culture system. Metabolic purification of cardiomyocytes (CMs) in glucose‐depleted and lactate‐enriched medium successfully eliminated residual undifferentiated stem cells, resulting in a refined CM population. Purified CMs never induced teratomas, and enriched CMs showed proper electrophysiological properties and calcium transients. Abstract : Cardiac regenerative therapy with human pluripotent stem cells (hPSCs), such as human embryonic stem cells and induced pluripotent stem cells, has been hampered by the lack of efficient strategies for expanding functional cardiomyocytes (CMs) to clinically relevant numbers. The development of the massive suspension culture system (MSCS) has shed light on this critical issue, although it remains unclear how hPSCs could differentiate into functional CMs using a MSCS. The proliferative rate of differentiating hPSCs in the MSCS was equivalent to that in suspension cultures using nonadherent culture dishes, although the MSCS provided more homogeneous embryoid bodies (EBs), eventually reducing apoptosis. However, pluripotent markers such as Oct3/4 and Tra‐1‐60 were still expressed in EBs 2 weeks after differentiation, even in the MSCS. The remaining undifferentiated stem cells in such cultures could retain a strong potential for teratoma formation, which is the worst scenario for clinical applications of hPSC‐derived CMs. The metabolic purification of CMs in glucose‐depleted and lactate‐enriched medium successfully eliminated the residual undifferentiated stem cells, resulting in a refined hPSC‐derived CM population. In colony formation assays, no Tra‐1‐60‐positive colonies appeared after purification. The nonpurified CMs in the MSCS produced teratomas at a rate of 60%. However, purified CMs never induced teratomas, and enriched CMs showed proper electrophysiological properties and calcium transients. Overall, the combination of a MSCS and metabolic selection is a highly effective and practical approach to purify and enrich massive numbers of functional CMs and provides an essential technique for cardiac regenerative therapy with hPSC‐derived CMs.